BOOK REVIEW: ANDRA VASILESCU, MIHAELA-VIORICA CONSTANTINESCU, GABRIELA STOICA, JONATHAN RUSSELL WHITE (EDS.) "EXPLORING DISCOURSE PRACTICES IN ROMANIAN". NEWCASTLE UPON TYNE: CAMBRIDGE SCHOLARS PUBLISHING, 2020, 460 P. - MANOLE, Veronica (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Published in 2020 at Cambridge Scholars Publishing, Exploring Discourse Practices in Romanian, edited by Andra Vasilescu, Mihaela-Viorica Constantinescu, Gabriela Stoica, and Johnathan Russell White, gathers in a collective volume contributions written in English by Romanian scholars who specialize in pragmatics and discourse analysis. This noteworthy initiative serves the important purpose, in our opinion, of giving an international visibility to Romanian linguistic research that may otherwise find itself confined to the frontiers of the Romanian language. The papers included in this volume are signed by well-established researchers, such as Andra Vasilescu, Ariadna Ștefănescu, Liana Pop or Margareta Manu Magda, but also by linguists belonging to what we might call the younger generation of Romanian pragmaticians and discourse analysis scholars.